Wartość zdrowia. Wybrane aspekty edukacji zdrowotnej na lekcjach języka polskiego w klasach IV-VIII = The value of health. Selected aspects of health education in Polish language classes in grades IV-VIII - Klimek, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes selected aspects of health education in Polish language lessons in classes IV-VIII of primary school. The paper proposes activities in the field of health promotion and health education, which can be implemented as part of literary, cultural and linguistic education, creation of statements or students? self-education. The author also draws attention to psychosocial health and the development of life skills in children and adolescents.
Keywords: edukacja zdrowotna; zdrowie; promocja zdrowia; wartości witalne; edukacja; szkolnictwo podstawowe; język polski; health education; health; health promotion; vital values; education; elementary education; Polish language